Concentrations of PAHs and other gaseous pollutants in the atmosphere of a rural area. Issue 9 (28th July 2016) - Jakovljević, Ivana; Pehnec, Gordana; Šišović, Anica; Vađić, Vladimira; Davila, Silvije; Godec, Ranka
ABSTRACT: In this study, concentrations of polycyclic aromatic hydrocarbons (PAHs) bound to PM10 particles were measured in a Croatian rural area. Considering that by now only a limited number of studies have provided data on pollutant concentrations for rural areas, our aim was to do so by determining the PAH levels, their mutagenic effect and relationship with meteorological conditions and other gaseous pollutants (NO, NO2, NH3 ). In this investigation, samples of PM10 particles were collected on quartz filters for 1 month in the cold period and 1 month in the warm period of the year, 24 h a day. Diagnostic PAH concentration ratios and factor analysis were used as tools to identify and characterize the PAH sources. The PAHs found in the warm period of the year were characteristic for car exhaust emissions while the predominant source of these pollutants in the cold period was wood burning. The measurements showed much higher average concentrations of all PAHs in the cold period, most pronounced for fluoranthene 0.347 ng m −3 and pyrene 0.223 ng m −3 . Mass concentrations of benzo(a)pyrene in the cold period ranged from 0.057 to 1.526 ng m −3, while in the warm period they varied from 0.009 to 0.111 ng m −3 . Mutagenicity related to BaP (BaPMeq ) was significantly higher during the cold period (1.095 ng m −3 ) than in the warm period (0.101 ng m −3 ).